Oral diseases and treatment outcome among diabetics that attended a Nigerian hospital - Egwuom, P. O.; Adamu, V. E.; Mgbeokwere, U.; Akubude, D. C. (Orapuh Journal, 2020)
IntroductionThe growing prevalence of diabetes may have a negative impact on oral health. Severe periodontitis has been considered the sixth complication of diabetes mellitus. Periodontitis, which is a serious challenge to oral clinicians, usually leads to impaired oral function.Purpose The purpose of this study was to assess the relationship between oral diseases and treatment outcome among diabetic patients that attended IMSUTH, Orlu, Nigeria.Materials & methodsThis 4-year retrospective study was carried out to study 262 patients. All the patients were previously diagnosed with diabetes mellitus by the medical units of the hospital. Patients’ response to treatment and blood-glucose levels were monitored till completion of treatment. Data retrieved included data on demographics, presenting complaints, Blood-glucose levels and treatment outcome. A self-designed data collection schedule form (DCSF) was used to record all observations.ResultsMajority of the patients were male (61.07%) and elderly with 40.1% and 34.4% of all patients studied falling into 61 – 70 years and 71 – 80 years age group, respectively. Major complaints among the patients were: pain (25.6%), halitosis (23.7%), tooth mobility (20.9%) and gum recession (14.9%). Treatment given to the patients included periodontal therapy (97%), restoration (5%) and extraction and replacement (20%). Fasting blood-glucose level of majority of the patients fell between 100 – 160 mg/dl. 87.6% patients responded positively to treatment while 12.4% did not. There was a significant relationship between the presenting complaints of patients and treatment outcome (p<0.005). However, there was no significant relationship between blood-glucose levels of patients and treatment outcome (p>0.005).ConclusionsData revealed that majority of patients in this study manifested periodontal disease. This calls for oral health education and interdisciplinary management of diabetes targeted at the prevention of oral complications of diabetes mellitus and this will help the diabetologist in the effective management of hyperglycaemia.